Strategi Komunikasi Pemasaran Melalui Instagram (Studi Deskriptif Kualitatif Akun @rengganis_basic) - Luluk Ita Ulfiah; Djoko Supriatno (Program Studi Ilmu Komunikasi, 2023)
Social media marketing that is done online has emerged as a means of communication that is rife today, namely by shopping via the internet. One of the social media platforms used is Instagram by utilizing Instagram as a social media platform is a marketing strategy that has been successful in benefiting its users. The focus of the problem of this research is to explain how the marketing communication strategy through Instagram is carried out by Rengganis Basic. While the purpose of this study is to find out how the marketing communication strategy through Instagram is carried out. This study uses a descriptive qualitative approach by analyzing the practice of buying and selling online. Data collection techniques in this study were observation, interviews, literature studies and documentation. The results of this study are that the communication process carried out in marketing its products through Instagram social media is by implementing a communication strategy that includes communication components (sources, messages, media, recipients, effects, feedback), applying the 4P marketing principles (product, price, place, promotion) The marketing communication strategy used by @rengganis_basic through Instagram includes determining target consumers, marketing content, using attractive images, good response to customers and promotions or discounts on Instagram.